Adult Cognitive Outcomes Following Childhood Mild Traumatic Brain Injury: A Scoping Review. Issue 5 (21st September 2022) - Chadwick, Leah; Peckham, S. Benjamin; Yeates, Keith Owen
Abstract : Objective: This review aimed to (1) summarize the existing literature regarding cognitive outcomes in adults with a history of pediatric mild traumatic brain injury (mTBI) and (2) identify gaps in the literature to provide directions for future research. Participants: Participants sustained mTBI in childhood (0-17 years of age) and underwent cognitive assessment in adulthood (older than 18 years) at least 1 year postinjury. Design: MEDLINE Ovid and PsycINFO Ovid databases were searched to identify original research studies that examined adult cognitive outcomes after childhood mTBI. Main Measures: Cognitive outcome measures assessed memory, attention, visuospatial abilities, processing speed, comprehension, reasoning, intellectual functioning, and executive functioning. Outcome measures ranged from self-reported cognitive symptoms to objective testing. Results: A total of 4216 articles were screened, leading to the inclusion of 6 published studies for review (3 prospective cohort and 3 retrospective cohort), with 131 537 participants (mTBI = 6724; controls = 123 823). Review of the included articles suggests that adults with a history of childhood mTBI perform within the average range expected for adult cognitive functioning, although they may perform more poorly than non–head-injured comparison groups on a variety of cognitive measures. Injury-related factors, such as requiring electroencephalography within 24 hours of injury and posttraumatic amnesia lasting longer than 30 minutes, may be associated with variability in adult cognitive outcomes. Conclusion: The weight of the available evidence suggests that childhood mTBI does not have a significant impact on adult cognitive functioning. However, further research is needed to provide a more comprehensive understanding of the long-term cognitive outcomes of childhood mTBI and to identify predictors of those outcomes in adulthood.